The Muslim community and English law - Poulter, Sebastian (Islam and Christian-Muslim relations, 1992)
This article addresses what are perceived as being the main areas of English law likely to present Muslims in Britain with problems or difficulties. Some English legal provisions relating to the family, education and religious freedom are inconsistent with Islamic beliefs and practices. While English law has to be obeyed by all those living in England, there are plenty of opportunities for Muslims to exploit its liberal principles and practical flexibility to suit their own needs. Furthermore, English law can be reformed to make it more consonant with the values and traditions of minority faiths, as the Sikhs have recently demonstrated. So far, Muslim pressure groups have failed to achieve similar reforms and some possible explanations for this are given. The future emphasis of the English legal system should lie in promoting cultural and religious pluralism, within a set of shared core values, and various concrete suggestions for change are offered. This article is based on a paper given at Cumberland Lodge, Windsor on 29 November 1991 to a conference on Islam: The British Experience' organized by the St. Catherine's Foundation.